The Role of Education - Belize at 41 Public Talk - "Belize Finally Breaking the Chains of Colonial Thought at 41" - De Shield, Christopher (My University, 2022)
Belize’s systematic exploitation under British colonialism has left a legacy of poverty and underdevelopment the country has yet to surmount. For Belize, decolonisation is an ongoing process. Education is routinely cited as a means for social and economic uplift and the key to emancipation from mental slavery. In this short talk, I argue simply that the Arts and Humanities are central to this emancipatory process. Belize’s decolonisation agenda will only be served by encouraging greater empathetic, critical questioning, big thinking, historical awareness, skilful communication, and the ability to appreciate nuance and celebrate difference. To the extent that the new curriculum fosters the type of thinking humanities subjects provide through the inclusion of arts competencies will it support efforts to articulate Belizean identity, take up the challenge of decolonisation, and engage learners in the life-affirming and future-friendly education we need to confront the debilitating legacies of colonialism and other looming global challenges.
Keywords: decolonisation; education; Arts and Humanities; new curriculum